Stock Literacy Education Through the Utilization of Digital Applications to Enhance Investment Interest among Generation Z in Banda Aceh - Pristiwa, Nara; Fatma, Surya; Mazas, Ichsan Akmal; Fitri, Aida; Ramiady, Luthfiar (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2025)
This community service program aims to enhance stock literacy among Generation Z in Banda Aceh through the utilization of digital investment applications. Generation Z is widely recognized as a technologically literate group, yet their knowledge and awareness of investment, particularly in the stock market, remain limited. To address this issue, the program was designed in the form of interactive education and training, focusing on the fundamentals of stock investment, practical guidance on using digital stock applications, and simple strategies for responsible investing. The methods employed included socialization, direct demonstrations of application usage, and hands-on mentoring. The results of this activity indicate an improvement in participants’ understanding of stock investment concepts and an increased interest in engaging with digital investment platforms that are legal and trustworthy. It is expected that this initiative will encourage Generation Z in Banda Aceh to become more financially literate, actively participate in the capital market, and contribute to both local and national economic growth.